Antihypertensive and Target-Organ Protective Properties of Telmisartan and Hydrochlorothiazide Single-Pill Combination - O. D. Ostroumova; A. I. Kochetkov (Рациональная фармакотерапия в кардиологии)
The most important result of the revision of the European and Russian guidelines for the management of arterial hypertension (AH) was a special focus on initializing antihypertensive treatment with single-pill combinations (SPCs) in majority patients with AH. Combination of the angiotensin II receptor blocker and thiazide diuretic is one of the possible first line SPCs in the absence of specific clinical conditions according to the new guidelines. In this regard, SPC of telmisartan and hydrochlorothiazide (HCT), worth special noticing in the classes of sartans and thiazide diuretics, since both drugs have a long clinical experience and large body of evidence of antihypertensive efficacy and safety, as well as telmisartan also has a number of superior target-organ protective and metabolic properties distinguishing it from other members of the class. In real clinical practice TANDEM study telmisartan and its SPC with HCT showed high antihypertensive efficacy and good tolerability in patients with all AH grades and with isolated systolic AH and allowed to achieve target blood pressure levels in the most of patients. Long-lasting effect is another essential characteristic of telmisartan, this feature allows to control blood pressure throughout the day, including the morning surge, which is the most “dangerous” in terms of cardiovascular risk. Telmisartan also provide powerful target-organ protection realized at the level of all AH target-organs. Finally, another unique pharmacological property of telmisartan and its combination with HCT is a favourable effect on the carbohydrate and lipid profile, which comprises of increasing tissue sensitivity to insulin, normalizing blood glucose levels, reducing blood total cholesterol, low-density lipoprotein cholesterol and triglycerides and thereby reducing risk of atherosclerosis development and progression. Telmisartan/HCT SPC should be recommended for wide use in hypertensive patients to control blood pressure, protect end-organs, improve prognosis and reduce cardiovascular risk due to its high antihypertensive efficacy, the ability to provide the large target-organ protection and a beneficial metabolic effect.